Korelasi Antara Sifat Fisikokimia dengan Potensi Cemaran Mikrobiologi pada Siomay di Kota Bandar Lampung - Apriana, Fera; Rahmadi, Isnaini; Syafitri, Yosi (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2023)
Siomay is a snack made mostly from fish, tapioca flour and other spices by steaming. People are interested in siomay because the price is relatively cheap, tastes good, is easy and practical to consume. However, siomay are susceptible to contamination by various pathogenic bacteria because they are sold freely without paying attention to the cleanliness of the seller's environment. In addition, unhygienic management can cause contaminants such as Staphylococcus aureus which can cause health problems. The purpose of this research was to determine the extent of TPC and Staphylococcus aureus contamination and to determine the relationship between chemical properties and microbial growth in siomay sold in Bandar Lampung City. The results showed that all siomay samples exceeded the maximum TPC and Staphylococcus aureus limits set by SNI. According to SNI 7756-2013 concerning siomay the maximum of TPC and Staphylococcus aureus in siomay is 5 x 104 CFU/mL and 1 x 102 CFU/mL respectively.The results of chemical and microbiological correlation tests show that water activity has a correlation with ALT and Staphylococcus aureus, pH has a correlation with Staphylococcus aureus, while aw has no correlation with ALT and Staphylococcus aureus.